Growing N-doped multiphase TiO2 nanocomposites on reduced graphene oxide: Characterization and activity under low energy visible radiation. Issue 5 (October 2017) - Y. Ozer, Lütfiye; Shin, Yuyoung; Felten, Alexandre; Oladipo, Habeebllah; Pikuda, Oluwadamilola; Muryn, Christopher; Casiraghi, Cinzia; Palmisano, Giovanni
Graphical abstract: Highlights: N-doped brookite-rutile were grown on reduced graphene oxide through a sol-gel method. 4-Nitrophenol was used as a model pollutant in water. The optimal loading of reduced graphene oxide was found to be 1%. PL at 1% graphene is minimal due to limited electron-hole recombination. Abstract: Reduced graphene oxide (G) was used as a platform to grow a mixed catalyst made of brookite and rutile nanoparticles doped with nitrogen, resulting in excellent performance for the oxidation of 4-nitrophenol (4-NP) in water under low energy (>425 nm) radiation. The samples were fully characterized by X-Ray Diffractometry (XRD), Raman Spectroscopy, Electron Microscopy, X-Ray photoelectron spectroscopy (XPS), photoluminescence (PL), Z-potential analysis, UV–vis Diffuse Reflectance Spectrophotometry (UV–vis DRS), and porosimetry. The improved hole-electron separation, demonstrated by PL, is boosted by the exceptional properties of reduced graphene oxide, which attracts and conveys electrons to dissolved oxygen, in turn initiating the oxidation process. The optimal amount of reduced graphene oxide was found to be 1% w/w based on 4-nitrophenol (4-NP) conversion rates. No leaching of carbon into water was revealed, even under irradiation, pointing to the suitability of the composite catalyst in water.